Survey of Knowledge on Injury Treatment in Students of State High School of Sports East Java - MOCHAMAD GUFRON; DONY ANDRIJIANTO (Journal of Physical Education For Secondary Schools, 2022)
Introduction: there are still many injuries experienced by students in education. As is the case at the Sports State High School, there are various kinds of fields, some of which are made of cement, grass, sand, etc.; each area has different injuries from one student to another; therefore, students must know more about the impact and risks from the field so that students can be more anxious when carrying out the training program. Purpose: This study aimed to determine the knowledge of the handling of injuries in SMA Negeri Sports East Java students. The type of research in this article uses descriptive quantitative. Methods: The method used by the researcher is using the survey method, which is a method used to examine current events or phenomena that are currently happening. The instrument used is a questionnaire in the form of multiple-choice questions, as many as 31, adopted from previous researchers. The population used was 78 students, while the selected sample was the entire population with a total sampling type sample because the researcher took the sample as a whole, so he used this type of sample. Â Results: From the results of the data analysis, the discussion, and research results, it can be concluded that the knowledge level of students in classes XI MIPA 1, XI MIPA 2, XI IPS 1, and XI IPS 2 at SMA Negeri Sports East Java is in the "low" category 100% with a frequency of 78 students. The "deficient" category is 92.3% with a frequency of 72 students; the "high" class is 25.6% with 20 students. So the overall level of students' knowledge of first aid for sports injuries in the school environment can be categorized as low. Conclusions: The statement above shows that students in schools have not been entirely taught about first aid for injuries. Still, students know little about first aid for damages; as evidenced by the data results above, the category of students receiving learning about first aid for injuries is low.